Octreotide (somatostatin analog) treatment reduces endothelial cell dysfunction in patients with diabetes mellitus - Clemens, Andreas; Klevesath, Martina; Hofmann Bowman, Marion; Raulf, Friedrich; Henkels, Mechthild; Amiral, Jean; Seibel, Markus J.; Zimmermann, Jürgen; Ziegler, Reinhard; Wahl, Peter; Nawroth, Peter Paul (Metabolism, 1999)
Octreotide is a long-acting somatostatin analog that has been shown to have various effects in diabetes. This study was performed to evaluate whether octreotide affects the vascular complications of diabetes mellitus. Albuminuria and serum thrombomodulin were used as markers of vascular and renal dysfunction. We studied the effect of octreotide in 27 patients with insulin-dependent diabetes mellitus (IDDM).
Gesehen am 18.06.2021